Indoor air bacterial load and antibiotic susceptibility pattern of isolates at Adare General Hospital in Hawassa, Ethiopia - Atalay, Yibeltal Assefa; Mengistie, Embialle; Tolcha, Alemu; Birhan, Belete; Asmare, Getachew; Gebeyehu, Natnael Atnafu; Gelaw, Kelemu Abebe (Frontiers in Public Health, 2023)
Background Air is the agent of pathogenic microbes that cause significant problems in the hospital environment. Multidrug resistance poses a major therapeutic challenge to these airborne microorganisms in hospital indoor environments. Method and materials This study was conducted at Adare General Hospital in Hawassa City, Sidama, Ethiopia. A cross-sectional study was conducted. The proportional allocation method was used to select the sampled 50 rooms from the total available rooms in each category of wards and staff offices. A total of 100 indoor air samples were collected using settle plates in all units twice a day, morning (9:00–4:00 a.m.) and afternoon (3:00–4:00 p.m.). The types and number of colonies were determined in the laboratory, and the pathogenic bacteria were isolated by appropriate bacteriological techniques. Antimicrobial susceptibility testing was performed on Mueller-Hinton agar for each potentially pathogenic bacterium isolated. For each bacterium, a total of 12 antibiotics were tested using the Kirby-Bauer disk diffusion method. The test organism was adjusted to McFarland turbidity standards of 0.5. Data were entered and analyzed using the SPSS version 25 window. Descriptive analysis and one-way analysis of variance were performed. Results The indoor air bacterial load of Adare General Hospital was found in the range between 210 and 3,224 CFU/m3. The highest indoor air bacterial load was identified from the gynecology ward with a mean of 2,542.5CFU/m3 at p < 0.05. From 100 indoor air samples, a total of 116 bacterial pathogen isolates were obtained. Gram-positive isolates predominated at 72.4%, of which 37.1% were Staphylococcus aureus, 26.7% were coagulase-negative Staphylococci, and the rest 8.6% were Streptococcus pyogenes. The isolation of pathogenic bacteria Staphylococcus aureus and coagulase-negative Staphylococci showed a high level of resistance to ampicillin. Conclusion A high bacterial load was found in the study area as compared to different indoor air biological standards. Staphylococcus aureus and coagulase-negative Staphylococci were the isolated predominant bacteria. Attention should be given to preventing and minimizing those environmental factors that favor the multiplication of bacteria in the indoor environment of a hospital for the safe health of patients, visitors, and staff.